Dynamic evaluations of heat pump and micro combined heat and power systems using the hardware-in-the-loop approach. (March 2020) - Mehrfeld, Philipp; Nürenberg, Markus; Knorr, Martin; Schinke, Lars; Beyer, Maximilian; Grimm, Manuel; Lauster, Moritz; Müller, Dirk; Seifert, Joachim; Stergiaropoulos, Konstantinos
Abstract: The seasonal coefficient of performance ( SCOP ) of a heat pump is nowadays determined according to standards on the basis of steady-state measurements in laboratories. Monitoring data from field tests show non-negligible deviations regarding SCOPs compared to values identified according to state-of-the-art standards. Observed deviations are partly due to neglecting instationary effects during momentary efficiency measurements of standards. To counter this problem, three institutes have collaborated on developing a novel dynamic testing procedure making use of the hardware-in-the-loop (HiL) concept. Furthermore, the control volume for the energy balance is extended to the whole system including the energy conversion system's controller. The energy conversion system is coupled via adequate test benches to a real-time building performance simulation. In order to evaluate the annual efficiency according to the HiL approach, the experiments demand a feasible time frame. For this purpose, we apply the k-medoids algorithm to shrink down one year to four representative days. We call the novel approach Dynamic System Evaluation (DSE) test. In this work, we compare the annual efficiency factors of three energy conversion systems: a micro combined heat and power system (mCHP), a ground-source heat pump (GSHP) and an air-source heat pump (ASHP). For this purpose, we use three different types of building performance simulation software as well as three different test facilities. The systems were investigated on two test benches each and result in annual efficiencies with relative deviations of Δ η rel, mCHP, HiL = 0.6 %, ΔSCOP rel, GSHP, HiL = 0.9 % and ΔSCOP rel, ASHP, HiL = 11.3 % . Highlights: Three systems: micro combined heat and power, ground-source and air-source heat pump. Annual efficiencies show deviations between standards and field test measurements. Hardware-in-the-loop method to gain realistic annual efficiencies. Validation via round robin test (3 different test benches and simulation tools). Relative deviations: 0.6% for mCHP, 0.9% for GSHP and 11.3% for ASHP.